(untitled) (Bangladesh Journal of Agricultural Research, 2015)
An intercropping experiment was conducted on hill valley at Hill Agricultural Research Station, Ramgarh and Kharachari during two consecutive rabi seasons of 2012-13 and 2013-14 to select suitable local bush bean cultivar for intercropping with hybrid maize in hilly areas of Bangladesh. Seven intercropping treatments viz., T1 = Normal maize spacing (75 cm × 25 cm) + 2 rows black seeded bush bean,T2 = Normal maize spacing (75 cm × 25 cm) + 2 rows pink seeded bush bean,T3 = Maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows black seeded bush bean,T4 = Maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows pink seeded bush bean, T5 = Maize wider spacing (100 cm × 50 cm) with 2 plants/hill + 3 rows black seeded bush bean, T6 = Maize wider spacing (100 cm × 50 cm) with 2 plants/hill + 3 rows pink seeded bush bean and T7 = Sole maize spacing (75 cm × 25 cm) were used. Sole hybrid maize produced the highest grain yield at both the locations. Bush bean cultivars in intercropped situation depressed hybrid maize yields by 7.15-37.29% at Ramgarh and 2.56-37.51% at Khagrachari compared to sole hybrid maize. The highest maize equivalent yield of 23.10 t/ha at Ramgarh and 24.08 t/ha at Khagrachari was recorded in maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows pink seeded bush bean combination (T4). The same treatment also showed the highest gross return (Tk 277200/ha at Ramgarh and Tk 288960/ha at Khagrachari), gross margin (Tk 180050/ha at Ramgarh and Tk 191810/ha at Khagrachari) and benefit cost ratio (2.85 at Ramgarh and 2.97 at Khagrachari). The result revealed that maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows pink seeded bush bean could be suitable and economically profitable for hybrid maize and bush bean intercropping in hill valleys of Bangladesh. Bangladesh J. Agril. Res. 40(2): 325-332 June 2015